Efeitos da melatonina e do extrato padronizado de Angelica keiskei e Panax ginseng sobre a performance física - Flor Neves, Ana Júlia (2025)
Herbal extracts of Panax ginseng (P. ginseng) and Angelica keiskei (A. keiskei) demonstrate ergogenic potential, promoting fatigue reduction with a chronic effect on increasing mitochondrial content. Melatonin also stands out for its ability to improve mitochondrial function and energy metabolism acutely, both of which are beneficial in endurance exercise. This study analyzed the ergogenic effect of a standardized herbal extract of A. keiskei and P. ginseng, as well as melatonin, to determine whether the combination of these substances improves performance compared to their use alone. The experiments were divided into two phases. Experiment I investigated the effects of the herbal extract of A. keiskei and P. ginseng on tissue and serum markers, without the influence of exercise. Experiment II evaluated the ergogenicity of the herbal extract and melatonin, as well as their combination. Sixty 45-day-old Wistar rats were used: 1) two groups of non-exercised animals: control group (CT) and herbal group (FIT); and 2) four groups of exercised animals: exercised control (CTEx), exercised herbal (FEx), exercised melatonin (MEx), and exercised herbal extract + melatonin (FMEx). In experiment I, the administration of the herbal extract (FIT) or vehicle solution (CT) was performed via orogastric gavage for 21 days at 90 days of age, followed by euthanasia at 111 days of age. In experiment II, aquatic familiarization took place at 76 days of age, and the Critical Load Test in swimming exercise (CLT) at 86 days of age. At 90 days of age, the administration of herbal extract (FEx and FMEx) or vehicle solution (CTEx and MEx) began. At 111 days of age, melatonin (MEx and FMEx) or vehicle solution (CTEx and FEx) was administered intraperitoneally 30 minutes before the Time Limit Test (tlim) at 90% of the critical load intensity (iCC). This was followed by euthanasia for the collection of biological materials (blood, skeletal muscle tissue, and liver) for serum, intramuscular, and hepatic glycogen and triglyceride analyses. The level of statistical significance was set at 5%. In experiment I, the administration of the herbal medicine did not alter glucose and triglyceride levels, but increased glycogen in the white gastrocnemius and reduced it in the gluteus maximus and liver. Triglycerides decreased only in the red gastrocnemius. In the TCC, there was no difference between the groups in the parameters: load vs. time and iCC. In experiment II, melatonin, and herbal medicine alone increased swimming time in the tlim. Melatonin increased glucose and decreased glycogen in the white gastrocnemius and soleus muscles. While the herbal medicine decreased serum triglycerides in the liver, white gastrocnemius, and red gastrocnemius muscles, it also reduced glycogen content in the white gastrocnemius, red gastrocnemius, and soleus muscles. Administration of the combination resulted in an increase in tlim (FMEx > CTEx), increased glucose compared to the CTEx/FEx/MEx groups, and reduced glycogen content in the white and red gastrocnemius tissues (FMEx < CTEx). It is concluded that the administration of melatonin and herbal medicine caused ergogenicity with a cumulative effect when combined, with both compounds modulating the consumption of energy substrates differently.